The effects of feeding steers different levels of phosphorus, copper, vitamin D, and phytase on feedlot performance, slaughter characteristics, and apparent phosphorus digestibility - Hurley, Leigh Anne, author; Stanton, Tim L., advisor (Colorado State University. Libraries, 2001)
Four experiments were conducted to study the effect of feeding different levels of phosphorus, copper, vitamin D and phytase on the feedlot performance, slaughter characteristics, and apparent mineral digestibility of finishing steers. In experiment 1,284 steers were randomized by breed, blocked by weight, and assigned to one of four treatments: 1) 0.24% phosphorus (P) and 10 ppm copper (Cu), 2) 0.24% P and 56 ppm Cu, 3) 0.35% P and 10 ppm Cu, and 4) 0.35% P and 56 ppm Cu. Treatments were added to a whole com based finishing diet. Steers were weighed every 28 d throughout the trial and feed intake was recorded daily. At the termination of the study, slaughter data was collected. There were no differences seen between treatments for feedlot performance. Dressing percents differed (P<0.05) between treatments (60.69%, 60.56%, 60.11%, and 59.74%, 0.35% P and 56 ppm Cu, 0.35% P and 10 ppm Cu, 0.24% P and 56 ppm Cu, and 0.24% P and 10 ppm Cu, respectively). The effects of feeding different levels of phosphorus and vitamin D were studied in experiment 2. Experimental modeling was the same as experiment 1, with the exception that 283 steers were used. Treatments were: 0.24% P and 0 IU vitamin D (vit D), 0.24% P and 552 IU vit D, 0.35% P and 0 IU vit D, and 0.35% P and 552 IU vit D. There were no differences in feedlot performance. Feed and feces were collected during this trial to determine fecal output and apparent digestibility of phosphorus, magnesium, and calcium. There were no differences (P>0.05) observed. Experiment 3 was a completely randomized design using 288 steers. Treatments were: 0.29% and 0 FTU phytase, 0.31% P and 200 FTU phytase, 0.32% P and 400 FTU phytase, and 0.35% P and 0 FTU phytase. There were no differences for overall feedlot performance or slaughter data. Fecal phosphorus output was lowest for the 0.29% P and 0 FTU phytase treatment. Steers supplemented with 400 FTU phytase exhibited greater (P<0.05) apparent mineral digestiblities than the 0.35%P and 0 FTU phytase (90.45% vs. 51.32%). The 0.29% P and 0 FTU phytase exhibited greater (P<0.05) apparent digestibilities than the 0.35%P and 0 FTU phytase. Experiment 4 was a 3 x 3 Latin square designed to evaluate fecal output and apparent digestibility of phosphorus. Treatments were: 0.28% P and 0 FTU phytase, 0.28% P and 250 FTU phytase and 0.28% P and 500 FTU phytase. There were no differences between treatments for fecal mineral output or apparent digestibility, however, apparent digestibility was greater (P<0.05) for the 0.28% P and 500 FTU phytase treatment.
Keywords: livestock; animal sciences